2016
DOI: 10.1177/1077546316675038
|View full text |Cite
|
Sign up to set email alerts
|

Modal identification of arch dams using balanced stochastic subspace identification

Abstract: Dynamic characteristics extracted from ambient and forced vibration tests are always associated with some level of uncertainties because of unknown nature of applied forces, existence of ambient noises as well as measurement errors. Stochastic Subspace Methods are among the most accurate and consistent methods within the domain of operational modal analysis. In this research, a new technique for Operational Modal Analysis is proposed using Stochastic Realization Theory and Canonical Correlation Analysis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Recently, structural health monitoring (SHM) became an attractive research area, because of its ability to prepare a global check of the structure for damage detection and monitoring (Tarinejad and Damadipour, 2016; Tarinejad and Pourgholi, 2016). Various techniques of SHM are ranging from application of electrical techniques to structural dynamics procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, structural health monitoring (SHM) became an attractive research area, because of its ability to prepare a global check of the structure for damage detection and monitoring (Tarinejad and Damadipour, 2016; Tarinejad and Pourgholi, 2016). Various techniques of SHM are ranging from application of electrical techniques to structural dynamics procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilization diagram describes the poles (modes) of the system under different modal orders, which can separate the natural modes from the spurious ones. [ 39 ] Figures 16 and 17 show the stabilization diagram of the identified modes during the typhoons of Jongdari and Rumbia, respectively, in which the y ‐axis represents truncated model order. It can be observed that the stable modes, unstable modes, and noise modes are mixed because of ambient noise and systematic error.…”
Section: Dynamic Response Of Structure During Two Typhoonsmentioning
confidence: 99%
“…Operational modal analysis (OMA), also called output-only modal analysis, is used to determine the modal parameters of structural systems based on ambient vibration data. The OMA techniques in different time, frequency, and timefrequency domains, such as Peak Picking (PP), 1 Frequency Domain Decomposition (FDD), [2][3][4][5] Stochastic Subspace Identification (SSI), 6,7 wavelet transform (WT), [8][9][10][11] and FDD-WT, [12][13][14] assume that the input forces to the system are white noise. This is a limiting assumption, because structural vibrations observed during operation cannot always be considered as pure white noise excitation.…”
Section: Introductionmentioning
confidence: 99%